Elemental and Mineralogical Composition of the Western Andean Snow (18°S-41°S) - Alfonso, Juan A.; Cordero, Raul R.; Rowe, Penny M.; Neshyba, Steven; Casassa, Gino; Carrasco Cerda, Jorge Fernando; MacDonell, Shelley; Lambert, Fabrice; Pizarro, Jaime; Fernandoy, Francisco; Feron, Sarah; Damiani, Alessandro; et al. (My University, 2019)
The snowpack is an important source of water for many Andean communities. Because of its importance, elemental and mineralogical composition analysis of the Andean snow is a worthwhile effort. In this study, we conducted a chemical composition analysis (major and trace elements, mineralogy, and chemical enrichment) of surface snow sampled at 21 sites across a transect of about 2,500 km in the Chilean Andes (18-41 degrees S). Our results enabled us to identify five depositional environments: (i) sites 1-3 (in the Atacama Desert, 18-26 degrees S) with relatively high concentrations of metals, high abundance of quartz and low presence of arsenates, (ii) sites 4-8 (in northern Chile, 29-32 degrees S) with relatively high abundance of quartz and low presence of metals and arsenates, (iii) sites 9-12 (in central Chile, 33-35 degrees S) with anthropogenic enrichment of metals, relatively high values of quartz and low abundance of arsenates, (iv) sites 13-14 (also in central Chile, 35-37 degrees S) with relatively high values of quartz and low presence of metals and arsenates, and v) sites 15-21 (in southern Chile, 37-41 degrees S) with relatively high abundance of arsenates and low presence of metals and quartz. We found significant anthropogenic enrichment at sites close to Santiago (a major city of 6 million inhabitants) and in the Atacama Desert (that hosts several major copper mines).
Keywords: Snowpack; Enrichment factor